CONTEMPORARY ARCHITECTURE IN TYPOLOGY OF CAR WORKSHOP AND SHOWROOM BUILDINGS - Keng Sukaria Tanzil (Journal of Development and Integrated Engineering, 2022)
In the era of the 2000s, revolutionary building typologies emerged, with mass forms of buildings that developed beyond the usual boundaries of existing building typologies. For example, the typology of hospital buildings at this time may follow the typology of hotel buildings, or the typology of traditional Lombok buildings, which was originally a typology of rice barns, changing its function to become a full-fledged residential building which is still in the typology of rice barns but has made adjustments to the details. shape, opening, and use. As well as building materials. Likewise, in the development of the building typology of showrooms and car repair shops, typology can change by adopting other building typologies that experience adjustments regarding the function of space and design details that can accommodate the needs of showrooms and car repair shops. So that in the era when the building was designed and built, the showroom and car repair shop would become a building with a contemporary architectural typology. This is because there is a desire to make showrooms and car repair shop buildings different from showrooms and car repair shops of the same type so that they will become icons and attractions for users and consumers as well as entrepreneurs who have an interest in car affairs. This study aims to analyze the application of contemporary architecture to exhibition buildings and car repair shops.